Ultrasound stimulation effects on differentiation of mouse embryonic stem cells - Phang, Chun Liang (2014)
Many studies had been done on how ultrasound stimulation and showed the enhancement of differentiation of mesenchymal stem cells (MSCs). However there are limited studies on the effects of ultrasound stimulation on mouse embryonic stem cells (mESCs) differentiation. In this report, we showed that ultrasound stimulation on pushes mESCs spontaneous differentiation towards endodermal lineage. Our samples will be cultured for 8 days, where spontaneous differentiation would take place and ultrasound would be introduced from day 3 onwards. Continuous ultrasound of 30mW/cm2 and 300mW/cm2 intensities were introduced to respective samples for 10 minutes daily and their spontaneous differentiation was investigated with 4 gene markers, Brachyury-T (mesoderm), alpha-fetoprotein (endoderm), Nestin (ectoderm), and OCT-4 (pluripotency). Our results showed that ultrasound did not induce significant differences in gene fold changes for early mesoderm and ectoderm differentiation, and pluripotency levels. However endoderm samples which were treated with ultrasound produced a significant endodermal gene upregulation in endodermal gene as compared to the untreated controls. This signifies that ultrasound stimulation on mESCs differentiation tends to push mESC spontaneous differentiation towards the endodermal lineage.